Inter and intra-examiner reliability of musculoskeletal ultrasound scanning of Anterior Talofibular Ligament and ankle muscles - Chelsea Starbuck (Journal of Ultrasound, 2022)
Purpose: Although the function of subjects with chronic ankle instability (CAI) has been examined, structural analysis by ultrasound scanning of the structures surrounding the ankle is limited. Before such structural comparisons between injured and uninjured people can be made it is important to investigate a reliable measurement protocol of structures possibly related to CAI. The aim of this study was to investigate the inter-intra examiner reliability of ultrasonic characteristics of selected structures in healthy subjects. Methods: Eleven healthy participants were assessed by an experienced sonographer and inexperienced certificated examiner. Ultrasound images were collected of the ATFL length and ankle muscles of gastrocnemius medialis (GM), tibialis anterior (TA) and peroneals. Thickness was measured for the muscles, whilst cross-sectional area (CSA) was measured for the peroneals. Inexperienced examiner repeated the measurements a week later. Results: Inter-examiner reliability was excellent for all structures (ICC3,1 = 0.91-0,98). Intra-examiner reliability shows excellent agreement for all structures (ICC3,1=0.92-0.98) except GM (good agreement) (ICC3,1 = 0.82). LoA, relative to structure size, ranged from 1.38% to 6.88% for inter-reliability and from 0.07% to 5.79% for intra-reliability. Conclusion: This study shows a high level of inter-intra examiner reliability in measuring the structures possibly related to CAI. Future research has been planned to investigate the structural analysis in CAI by using applied MSUS protocol.